Impact of Probiotics as an Adjunct to Standard Therapy on Disease Activity and Inflammation in Mild to Moderate Rheumatoid Arthritis: A Randomized Controlled Trial - Ebtihal Bilal, Iqra Tahir Dar, Sabiha Arshad, Khaula Fiaz, Mobeen Ahmad Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Rheumatoid Arthritis (RA) is a chronic autoimmune disease marked by persistent inflammation and damage to joints. The conventional approach for treating RA includes DMARDs together with anti-inflammatory medications, although these drugs are not without side effects. There is some evidence that probiotics could reduce inflammation and modulate the immune system; therefore, they are usually considered as an adjunct treatment for RA. The purpose of this study is to evaluate the effectiveness of probiotic therapy along with standard treatment in comparison to standard treatment alone in patients suffering from mild to moderate RA. Methods: This randomized controlled trial recruited eighty patients diagnosed with mild to moderate RA. These patients were randomly allocated to either standard treatment alone (n=40) or standard treatment with concomitant probiotics (n=40) for a period of twelve weeks. The primary outcomes of disease activity were assessed using the DAS28 score along with CRP and ESR levels. Patients were evaluated at baseline, 6 weeks, and 12 weeks. Results: Patients who received probiotics along with standard treatment demonstrated significantly reduced DAS28 scores, CRP and ESR levels compared to the standard treatment only group at both 6 weeks and 12 weeks. Patients in the probiotic group also reported lower gastrointestinal medication-related side effects. Conclusion: For patients with mild to moderate rheumatoid arthritis (RA), adding probiotics to standard treatments substantially lowers disease activity and inflammation. Probiotics may also improve overall comfort. More research is necessary to confirm these findings and assess the impact of probiotics long-term. Keywords: Probiotics, Rheumatoid Arthritis, Disease Activity, Inflammation, Standard Therapy